ANALISIS BEBAN KERJA UNTUK MENGETAHUI JUMLAH PEKERJA OPTIMAL KARYAWAN DENGAN MENGGUNAKAN METODE WORK LOAD ANALYSIS DI PT. SURYA TOTO INDONESIA, TBK - Sutaarga, Ossa; Ramlan, Muhammad (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2020)
This research is focused on increasing productivity by optimizing total manpower in the HR field related to work activities and time needed by employees to complete their tasks in accordance with the Job Description given by management. The method used in this research is Work Load Analysis which is a picture of the workload needed in an organization in a company. With this method can provide information about the allocation of employee resources in completing workloads. PT. Surya Toto Indonesia is always trying to improve the quality of its products and services. If there is no particular attention to quality or productivity, the company will decline. The average productivity obtained from the measurement of productivity rose by 10%, with a test of the adequacy of the data N = 164, the level of accuracy of the data S = 6.2%, the level of confidence of the data of = 95%. Keywords: Workload Analysis, Human Resource Management.